Comprehensive Review on Low-Level Laser Therapy in Dentistry - Sameep Singh; Ayan Chakraborty; Anitta Rachel Saju; Rubal Singh; Anjali Sen; Shreya Shrinivas; Pratik Surana (Journal of Pharmacy and Bioallied Sciences)
Low-level laser therapy (LLLT) has broad applications in dentistry, enhancing patient outcomes through its anti-inflammatory, analgesic, and biostimulatory effects. It is used for reducing pain and swelling, accelerating wound healing, and promoting tissue regeneration. LLLT is effective in managing conditions, such as temporomandibular disorders (TMDs), oral mucositis, and postoperative discomfort. Additionally, it aids in orthodontics by accelerating tooth movement and mitigating associated pain. This non-invasive treatment offers a safe, efficient, and clinically proven approach, integrating well into various dental procedures to improve overall patient care and recovery.